English Teachers’ Assessment Practices in Differentiated Instruction - Ketut Merina Wati; Ni Luh Putu Eka Sulistia Dewi; Anak Agung Gede Yudha Paramartha (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study aims to describe how English teachers at SMA Negeri 3 Singaraja implement assessment in differentiated instruction. Using descriptive qualitative methods through observations and interviews, this study found that teachers utilize diagnostic, formative, and summative assessments to identify students' prior knowledge, monitor learning progress, and measure final achievement. Diagnostic assessments help teachers map students' readiness, interests and learning styles, while formative assessments allow teachers to provide feedback and adjust learning according to students' needs. Summative assessments are used at the end of learning to evaluate overall mastery of the material. This practice shows that assessment is not only a tool for assessing learning outcomes, but also supports student-centred learning and is aligned with Merdeka Curriculum. The findings emphasize the importance of integrating different types of assessments to create flexible learning, accommodate students' diverse abilities, and motivate students to improve their learning outcomes.